Information Security Behavior and Compliance with ISO 27001 in IT Companies - Rafli, Mohammad; Akhwat Nusantara, Nuansa Cinta; Putri, Ella Rosediana; Sari, Intan Pravda; Zamzami, Naufal; Muharroman, Aflahal Insan (Universitas Negeri Surabaya, 2024)
This article discusses the importance of information security behavior and the application of the ISO 27001 standard in the context of IT companies. Using PRISMA guidelines, we outline the important role of information security behavior in maintaining the integrity, confidentiality, and availability of necessary information within an enterprise. We introduce the ISO 27001 standard as the main framework for managing secure information systems, highlighting the main stages in its implementation: plan, do, and check. This study also identified factors that influence the implementation of information security behavior in IT companies, such as organizational culture, training, management supervision, and communication between departments. With a deep understanding and implementation of ISO 27001, companies can ensure the security of their information, which is the main goal of information security in the organizational context and information technology environment.